Motor Milestones and Autism Spectrum Disorder: Insights from Denver II-Based Assessments - Santoso, Yoga Budhi; Siregar, Ernie C; Novianti, Ranti; Astuti, Eka Yuli; Sptian, Fajar Indra (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
Motoric impairments are not among the primary challenges faced by children with autism spectrum disorder (ASD), but many studies have found that various motoric impairments are often encountered in children with ASD. This study focused on identifying the gap in gross motor milestones in children with ASD. The study involved 15 children with ASD, consisting of 14 boys and 1 girl, aged 3-6 years. After conducting a developmental screening using the Denver-II, it was found that the average gap in motor development wasapproximately 1 year and 7 months behind what is expected, with the three motor development tasks most frequently not mastered by children with ASD compared to typically developing children their age being the ability to throw a ball upwards, jump forward, and stand on one foot for a fewseconds.